Mechanisms of Public Administration to Ensure Investment and Innovation Security of Territories - Buryk Myroslav M. (Bìznes Inform)
For the rapid and successful regeneration of the Ukrainian economy against the background of crisis political and social phenomena and conditions of uncertainty, as well as its effective transformation in the European integration aspect, it is necessary to intensify security processes in the investment sphere. The study is devoted to a systematic and comprehensive definition of the specifics of managing the security of the innovation and investment sphere of territorial development under conditions of uncertainty. The article analyzes the strategy and system of financial instruments for ensuring investment and innovation development of Ukrainian regions in the conception of the potential of modern public administration mechanisms. The article analyzes the essence of the phenomenon of investment and innovation security, on the basis of which a qualitative assessment of the limits of the functionality of investment and innovation activities as components of economic security is formed. It is proved that in the realities of restriction of public finances, the creation of material and financial incentives for the development of territories in the sphere of innovation is seen as efficient. It is determined that the realization of the existing innovative potential of territories is considered efficient in the case of expanding the possibilities of investment activity. The expediency of positioning the conception of investment and innovation security as one of the guarantees of economic security of territories is substantiated, theoretical and methodological approaches to disclosing its meaning, essence and specificity are formed. The functional of investment and innovation security in the conception of increasing the level of competitiveness of the State is studied. The author analyzes the feasibility and prospects of using innovative electronic systems, the capabilities of modern tools and technologies to optimize the public administration system in the field of investment and innovation security. The results of the study have a certain practical functionality in the conception of transformation of the modern management paradigm on the basis of publicity and balanced development.